Strategi Penerapan Scaffolding Dengan Metode Problem Based Learning Pada Materi Topologi Jaringan Di SMA Negeri 3 Surakarta - Al-Fayed, Iqbal Isnan; Hatta, Puspanda; Jumari (Indonesian Journal of Learning and Instructional Innovation, 2024)
This study aims to analyze the effectiveness of applying scaffolding strategies with the Problem Based Learning (PBL) method in teaching network topology at SMA Negeri 3 Surakarta. The scaffolding strategy is used to support and enhance students' abilities to understand the basic concepts of network topology through gradual assistance tailored to the individual needs of the students. The PBL method is employed to encourage students to develop problem-solving and critical thinking skills by presenting real-life problem situations that must be solved collaboratively. This research uses a classroom action research (CAR) design with three cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observations, interviews, written tests, and questionnaires. The results of the study indicate that the use of scaffolding strategies with the PBL method significantly improves students' understanding of network topology and enhances their critical thinking and problem-solving abilities. Additionally, students demonstrated increased motivation and active engagement in the learning process. Therefore, scaffolding strategies combined with the PBL method are effective for teaching network topology at the high school level.